Ribavirin therapy for Chikungunya arthritis - Rajan Ravichandran, Manju Manian (The Journal of Infection in Developing Countries, 2008)
Background: Chikungunya is an acute viral infection presenting with a febrile episode and severe arthralgia, swelling of soft tissues, especially around the ankles. Many patients recover with nonspecific treatment of analgesics. Some patients continue to have subacute crippling arthritis in the legs affecting their mobility. This study was undertaken to see the effect of the antiviral drug Ribavirin in the clinical outcome of these patients.Methodology: Ten patients who continued to have crippling lower limb pains and arthritis for at least two weeks after a febrile episode were taken up for the drug study. Ten similar patients during the same period were included as controls. In the study group Ribavirin was given at 200 mg twice a day for seven days. Both groups were followed up for four weeks Results: All patients in the drug group reported improvement in the joint pains with six of them capable of walking freely. The soft tissue swelling also reduced in eight. In three patients the pain returned after mobilization. Seven patients continued not to receive analgesics after four weeks.Conclusions: Ribavirin may have a direct antiviral property against Chikungunya leading to faster resolution of joint and soft tissue manifestations.